Discourse on Reporting the Palestine-Israel Conflict “Inclusion Strategy in the News of the Shooting of Shireen Abu Akleh (Al Jazeera Journalist) on BBC Arabic Newspaper” - Nawawi, Hasby Achmad; Kulsum, Umi (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2023)
This study aims to analyze the inclusion strategy in constructing the news about the shooting of Al Jazeera journalist Shireen Abu Akleh. The method used is descriptive analysis with the object of research, namely news texts